Financial Performance of Small and Medium Sized Enterprises: A Systematic Literature Review - Syahrul Syarifudin; Sri Lestari; Dian Purnomo Jati; Sudarto Sudarto (International Journal of Economics, Business and Innovation Research, 2024)
This article uses a systematic literature review that aims to summarize several studies on financial performance of small and medium sized enterprises (SMEs). SMEs are very large for the growth of the global economy. This article uses the PRISMA (Preferred Reporting Items for Systematic Reviews) method. Data sources were obtained from Scopus for the period 2014-2023. The results obtained were 926 journals, then data reduction was carried out using exclusive and inclusive criteria so that 18 journals were reviewed. Results for variables related to SMEs Performance, Firm Performance, Open Innovation, Financial Performance, Innovation, managerial ties, big data, digital transformation etc. Overall, the authors hope that this research can be used as learning material and written reflections in the future.